2003
DOI: 10.1007/s00347-003-0808-0
|View full text |Cite
|
Sign up to set email alerts
|

Genexpression bei Keratokonus

Abstract: Our results indicate that keratoconus is a process in which repair and scar-formation mechanisms operate at the same time. As candidate genes for this mechanism, collagen IV and related proteoglycans were favoured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In support of this theory, alterations in the expression level of collagen type IV (α-4 chains) were observed in corneas inflicted by KC. [20,21] Matrix metalloproteinases (MMP) are the major expressed metalloproteases in the cornea. It has been demonstrated that the proteolytic activity of MMP increases in KC.…”
Section: Keratoconus (Kc) Is Defined As a Bilateral Non-inflammatory And Progressive Diseasementioning
confidence: 99%
“…In support of this theory, alterations in the expression level of collagen type IV (α-4 chains) were observed in corneas inflicted by KC. [20,21] Matrix metalloproteinases (MMP) are the major expressed metalloproteases in the cornea. It has been demonstrated that the proteolytic activity of MMP increases in KC.…”
Section: Keratoconus (Kc) Is Defined As a Bilateral Non-inflammatory And Progressive Diseasementioning
confidence: 99%